Teaching English Speaking by Increasing Vocabulary Through English Islamic Song Intonation - Zuhri, Syarifuddin; Patel, Kiran Bala (Darajatuna: Interdisciplinary Journal of Islamic Studies, 2025)
Vocabulary is a fundamental component of English language learning, supporting the development of listening, speaking, reading, and writing skills. However, many students struggle to acquire new vocabulary in a meaningful and enjoyable way. One engaging method to support vocabulary acquisition is through the use of English Islamic songs in the classroom.This study applied a qualitative classroom-based approach involving English Islamic songs as a learning medium. Students were exposed to selected Islamic-themed songs during structured listening and singing sessions. Activities were designed to highlight new vocabulary, rhythm, and grammatical patterns. Observations and student feedback were used to assess engagement and learning outcomes. The results indicated that students showed increased enthusiasm and focus during lessons. Repeated exposure to song lyrics allowed students to naturally memorize vocabulary and sentence patterns. Even students with limited comprehension were able to recall key phrases and words through consistent listening and participation. The familiar themes and simple language in Islamic songs made learning more relatable and less intimidating. The findings suggest that integrating Islamic songs into English teaching can be an effective tool to enhance vocabulary learning, especially in Islamic school settings. However, teachers must select songs carefully and design varied, interactive activities to ensure pedagogical effectiveness. While songs are not a replacement for formal instruction, they serve as a powerful supplement that can boost student motivation, vocabulary retention, and overall engagement.